2018
DOI: 10.1002/jrs.5381
|View full text |Cite
|
Sign up to set email alerts
|

Regulate the coupling reaction of 4‐nitrothiophenol to 4,4′‐dimercaptoazobenzene by organic alkali

Abstract: The coupling reaction of 4‐nitrothiophenol to 4,4′‐dimercaptoazobenzene was investigated by surface enhancement Raman scattering method. The reaction was found to be controlled by the compatibility of organic alkalis and silver nanoparticles. The effect of hot electron–hole pairs on the reaction was evaluated. Furthermore, the mechanism of organic alkalis affecting hot electron–hole pairs to achieve regulation of the coupling reaction of 4‐nitrothiophenol to 4,4′‐dimercaptoazobenzene was studied. A comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The reaction was found to be controlled by the compatibility of organic alkalis and silver NPs. A comprehensive analysis of the various SERS spectra collected was carried out . Merlen and co‐workers were able to follow the formation of cyanide compounds during the preparation of gold surfaces using SERS.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was found to be controlled by the compatibility of organic alkalis and silver NPs. A comprehensive analysis of the various SERS spectra collected was carried out . Merlen and co‐workers were able to follow the formation of cyanide compounds during the preparation of gold surfaces using SERS.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…A comprehensive analysis of the various SERS spectra collected was carried out. [41] Merlen and co-workers were able to follow the formation of cyanide compounds during the preparation of gold surfaces using SERS. They also demonstrated that high power laser illumination transforms these toxic compounds into carbon species, and this method can be used to clean SERS substrates.…”
Section: Sers Substratesmentioning
confidence: 99%